A composite thermal insulation material of ceramic fiber and aerogel and preparation method thereof

Through the preparation method of composite thermal insulation material of ceramic fibers and aerogels, the problems of reduced thermal insulation performance, insufficient toughness, and easy particles falling off in humid environments are solved, and the performance uniformity of composite thermal insulation materials and the improvement of various properties are achieved.

CN119263794BActive Publication Date: 2025-03-25SHANDONG RES & DESIGN ACADEMY OF IND CERAMICS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411795745.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-25
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

Silicon-based aerogels have reduced thermal insulation performance, insufficient toughness, and easy particles to fall off in humid environments, resulting in poor durability, uneven performance of composite thermal insulation materials, insufficient thermal shock resistance and high temperature resistance.

Method used

By preparing composite heat insulation materials between ceramic fibers and aerogels, the preparation of primary and secondary aerogel solutions, treatment of ceramic fibers, and preparation of modified silicon carbide whisker suspensions, the uniform composite and cross-linking of ceramic fibers and aerogels is achieved, and the hydrophobicity, toughness, durability, thermal shock resistance and high temperature resistance of the material are improved.

Benefits of technology

The prepared composite heat insulation materials have uniform properties, low thermal conductivity, large water contact angle, good toughness and durability, significantly improved thermal shock resistance and high temperature resistance, meeting the application needs of composite materials in various environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a composite thermal insulation material of ceramic fiber and aerogel and a preparation method thereof, belonging to the technical field of composite thermal insulation materials. The preparation method comprises the following steps: preparing a primary aerogel solution, performing a primary treatment, preparing a secondary aerogel solution, performing a secondary treatment, preparing a modified silicon carbide whisker suspension, and compounding; the preparation of the primary aerogel solution comprises the following steps: preparing coated graphite and mixing; the compounding comprises, in an argon atmosphere, completely immersing the silicon carbide fiber felt after the secondary treatment in the modified silicon carbide whisker suspension, and standing at 55-60 DEG C; then adding the felt into a high-pressure reactor and performing supercritical drying with carbon dioxide; and finally adding the felt into a tubular furnace and performing high-temperature treatment to obtain a composite thermal insulation material; the composite thermal insulation material prepared by the invention not only has good thermal insulation, hydrophobicity, toughness and durability, and uniform performance, but also has good thermal shock resistance and high temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite thermal insulation materials, and in particular to a composite thermal insulation material of ceramic fiber and aerogel and a preparation method thereof. Background Art

[0002] Thermal insulation materials refer to materials that can block the transfer of heat flow, also known as thermal insulation materials. Traditional thermal insulation materials mainly include glass fiber, asbestos, rock wool and silicate, etc. New thermal insulation materials mainly include aerogel and vacuum insulation materials. At present, the most commonly used thermal insulation material is aerogel. Aerogel refers to a nano-scale porous solid material formed by using a sol-gel method and a certain drying method to replace the liquid phase in the gel with gas. It has high porosity and low density, so it has excellent thermal insulation properties. Aerogel is mainly divided into silicon-based aerogel, carbon-based aerogel, sulfur-based aerogel, metal oxide-based aerogel and metal-based aerogel, etc. Among them, the most commonly used aerogel is silicon-based aerogel.

[0003] However, the following problems exist in the use of silicon aerogels: first, silicon aerogels have poor hydrophobicity and are easy to absorb moisture. After absorbing moisture, the thermal insulation performance is greatly reduced, which limits the application of silicon aerogels in humid environments; second, silicon aerogels have low toughness and poor mechanical properties, which affects the application effect of silicon aerogels; third, since silicon aerogels have a porous structure and small internal particles, the particles of silicon aerogels are easy to fall off during use, which affects the durability of silicon aerogels.

[0004] In order to solve the above problems, the inventor tried to compound ceramic fiber with silicon aerogel, specifically, adding ceramic fiber felt to silicon aerogel solution for impregnation, curing and drying to prepare composite thermal insulation materials. Since ceramic fiber felt has good hydrophobicity and high toughness, the hydrophobicity and toughness of the prepared composite thermal insulation materials are improved. In addition, ceramic fiber felt can also play a role in fixing particles in silicon aerogel, thereby improving the durability of the composite thermal insulation materials. However, the prepared composite thermal insulation materials still have the following problems: First, when the ceramic fiber felt is added to the silicon aerogel solution for impregnation, there is an uneven impregnation, resulting in uneven performance of the prepared composite thermal insulation materials, which is specifically manifested in the uneven hydrophobicity and thermal insulation performance of the prepared composite thermal insulation materials; second, there are still a large number of hydroxyl groups on the surface of the composite thermal insulation materials prepared after the ceramic fiber and silicon aerogel are compounded, resulting in the general hydrophobicity of the prepared composite thermal insulation materials; third, there is a problem of small interaction force between ceramic fiber felt and silicon aerogel, and the interaction force is easily affected by temperature, resulting in poor thermal shock resistance of the prepared composite thermal insulation materials.

[0005] In order to solve the above problems, the existing methods mainly involve chemically modifying the ceramic fiber felt and the silicon-based aerogel, respectively, and introducing different chemical groups into the ceramic fiber felt and the silicon-based aerogel, respectively, so as to achieve uniform impregnation through non-covalent bonds between different chemical groups, and improve the interaction between the ceramic fiber felt and the silicon-based aerogel. In addition, by introducing highly hydrophobic chemical groups, the hydrophobicity of the composite thermal insulation material can also be improved. However, the introduced chemical groups have poor high temperature resistance and are easily decomposed at high temperatures, which affects the high temperature resistance of the prepared composite thermal insulation material. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a composite thermal insulation material of ceramic fiber and aerogel and a preparation method thereof. The prepared composite thermal insulation material not only has good thermal insulation, hydrophobicity, toughness and durability, uniform performance, but also has good thermal shock resistance and high temperature resistance.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing a composite thermal insulation material of ceramic fiber and aerogel, comprising the following steps: preparing a primary aerogel solution, performing a primary treatment, preparing a secondary aerogel solution, performing a secondary treatment, preparing a modified silicon carbide whisker suspension, and compounding;

[0009] The preparation of the primary aerogel solution comprises the following steps: preparing coated graphite, mixing;

[0010] The coated graphite is prepared by mixing silica sol and γ-aminopropyltriethoxysilane, stirring and refluxing at a stirring speed of 400-600 rpm at 40-45° C. for 5-6 hours, adding graphite powder, continuing to stir and reflux for 1-1.5 hours, centrifuging, controlling the centrifugal speed to be 6000-7000 rpm, the time to be 5-6 minutes, washing the precipitate with deionized water for 3-4 times, and drying to obtain the coated graphite;

[0011] In the preparation of the coated graphite, the volume mass ratio of silica sol, γ-aminopropyltriethoxysilane and graphite powder is 200-210 mL: 6-7 mL: 34-36 g;

[0012] The particle size of the graphite powder is 50 μm;

[0013] The average particle size of silicon dioxide in the silica sol is 22 nm, the pH is 9, and the mass content of silicon dioxide is 30%;

[0014] The mixing is to mix the silica sol and γ-aminopropyltriethoxysilane, stir and reflux at 40-45° C. and 400-600 rpm for 5-6 hours, add the coated graphite and nickel sulfate, and continue to stir and reflux for 50-60 minutes to obtain a primary aerogel solution;

[0015] In the mixture, the volume mass ratio of silica sol, γ-aminopropyltriethoxysilane, coated graphite and nickel sulfate is 2000-2100 mL: 60-70 mL: 50-55 g: 15-16 g;

[0016] The average particle size of silicon dioxide in the silica sol is 22 nm, the pH is 9, and the mass content of silicon dioxide is 30%;

[0017] The primary treatment comprises adding the silicon carbide fiber felt into a mold, adding the mold into a vacuum device, adding a primary aerogel solution, ensuring that the silicon carbide fiber felt can be completely immersed in the primary aerogel solution and allowing it to stand in a vacuum; then adding the silicon carbide fiber felt into an oven for heat treatment, and then adding the silicon carbide fiber felt into a tubular furnace for high-temperature treatment to obtain a silicon carbide fiber felt after the primary treatment;

[0018] In the one-time treatment, the vacuum degree of the vacuum tank during the vacuum standing is 100-200 Pa, and the vacuum standing time is 30-40 minutes;

[0019] The temperature of the oven during the heat treatment is 100-110°C, and the heat treatment time is 18-20h;

[0020] The high temperature treatment is carried out in an argon atmosphere, heating the temperature to 1450-1550°C at a heating rate of 4-5°C / min, and standing for 2-2.5 hours;

[0021] The weight of the silicon carbide fiber felt is 300 g / m 2 , thickness is 2mm;

[0022] The secondary aerogel solution is prepared by mixing silica sol and γ-aminopropyltriethoxysilane, stirring and refluxing at 40-45° C. at a stirring speed of 400-600 rpm for 6-7 hours to obtain a secondary aerogel solution;

[0023] In the preparation of the secondary aerogel solution, the volume ratio of silica sol and γ-aminopropyltriethoxysilane is 2000-2100:100-120;

[0024] The average particle size of silicon dioxide in the silica sol is 7 nm, the pH is 10, and the mass content of silicon dioxide is 30%;

[0025] The secondary treatment comprises adding the silicon carbide fiber felt after the primary treatment into a mold, adding the mold into a vacuum device, adding a secondary aerogel solution, ensuring that the silicon carbide fiber felt can be completely immersed in the secondary aerogel solution and allowing it to stand in a vacuum; then adding it into an oven for heat treatment; and then completely immersing it in anhydrous ethanol for aging treatment to obtain the silicon carbide fiber felt after the secondary treatment;

[0026] In the secondary treatment, the vacuum degree of the vacuum tank during the vacuum standing is 100-200Pa, and the vacuum standing time is 50-60min;

[0027] The temperature of the oven during the heat treatment is 50-55°C, and the heat treatment time is 50-60min;

[0028] The temperature during the aging treatment is 50-55°C, and the aging treatment time is 70-75h, with each treatment lasting 10-12h.

[0029] The modified silicon carbide whisker suspension is prepared by mixing β-type silicon carbide whiskers, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and anhydrous ethanol, stirring and refluxing at 60-65° C. and a stirring speed of 100-200 rpm for 3-4 hours, filtering, washing the precipitate with anhydrous ethanol for 3-4 times, drying, and then mixing with methanol, stirring at a stirring speed of 100-200 rpm for 20-30 minutes at room temperature to obtain a modified silicon carbide whisker suspension;

[0030] In the preparation of the modified silicon carbide whisker suspension, the mass volume ratio of β-type silicon carbide whisker, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, anhydrous ethanol and methanol is 100-110 g: 50-60 mL: 900-1100 mL: 8700-9000 mL;

[0031] The length of the β-type silicon carbide whisker is 20 μm and the diameter is 1 μm;

[0032] The composite comprises: in an argon atmosphere, completely immersing the secondary treated silicon carbide fiber felt in a modified silicon carbide whisker suspension, and standing at 55-60° C. for 5-5.5 hours; then adding the felt into a high-pressure reactor and performing supercritical drying using carbon dioxide; and finally adding the felt into a tubular furnace for high-temperature treatment to obtain a composite thermal insulation material;

[0033] In the composite, the mass volume ratio of the silicon carbide fiber felt after secondary treatment to the modified silicon carbide whisker suspension is 300g:3000-3200mL;

[0034] The temperature of the high-pressure reactor during supercritical drying is 45-50°C, the pressure is 10-12MPa, and the supercritical drying time is 2.5-3h;

[0035] The high temperature treatment is carried out in an argon atmosphere by heating the temperature to 800-850° C. at a heating rate of 4-5° C. / min and standing for 2-2.5 hours.

[0036] A composite thermal insulation material prepared by the above-mentioned preparation method.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) The method for preparing the composite thermal insulation material of ceramic fiber and aerogel of the present invention comprises preparing a primary aerogel solution, a primary treatment, preparing a secondary aerogel solution, a secondary treatment, preparing a modified silicon carbide whisker suspension, and compounding. The step of preparing the primary aerogel solution comprises a step of preparing coated graphite and a step of mixing. The step of preparing the coated graphite comprises using large-particle silica sol to coat graphite powder to obtain coated graphite, i.e., graphite powder coated with silica sol. The step of mixing comprises mixing the graphite powder coated with silica sol with large-particle silica sol to obtain a primary aerogel solution. The primary treatment comprises using the primary aerogel solution to impregnate the silicon carbide fiber felt, and then drying it and subjecting it to a high-temperature treatment in an argon atmosphere. During the high-temperature treatment, the graphite reacts with silica to form a silicon carbide fiber felt. The surface of the silicon carbide fiber felt is coated with a layer of silicon carbide nanowires to obtain a silicon carbide fiber felt after primary treatment; the secondary aerogel solution is prepared by treating the silica sol with γ-aminopropyltriethoxysilane to obtain a secondary aerogel solution with aminopropyl groups on the surface; the secondary treatment is to impregnate the silicon carbide fiber felt after primary treatment with the secondary aerogel solution with aminopropyl groups, and then perform heat treatment and aging to obtain the silicon carbide fiber felt after secondary treatment; the modified silicon carbide whisker suspension is prepared by using γ-(2,3-cyclohexane) The β-type silicon carbide whisker is treated with propyltrimethoxysilane to obtain β-type silicon carbide whiskers with epoxy groups on the surface, which are then mixed with methanol to obtain a suspension of β-type silicon carbide whiskers with epoxy groups on the surface, namely, a modified silicon carbide whisker suspension; the composite is to impregnate the silicon carbide fiber felt after secondary treatment with the modified silicon carbide whisker suspension in an argon atmosphere, perform supercritical drying, and then perform high-temperature treatment in an argon atmosphere to obtain a cross-linked product with silicon carbide nanowires and silicon carbide whiskers on the surface The middle layer is a composite of silicon carbide nanowires and silicon dioxide aerogel, and the inner layer is a composite thermal insulation material of silicon carbide fiber felt; the cross-linked product of silicon carbide nanowires and silicon carbide whiskers on the surface can improve the hydrophobicity, toughness, durability, thermal shock resistance, and high temperature resistance of the composite thermal insulation material. The purpose of coating a layer of silicon carbide nanowires on the surface of the silicon carbide fiber felt before impregnation with silica sol is to fix the silica sol and improve the dispersibility of the silica sol, thereby improving the thermal insulation of the composite thermal insulation material and ensuring the uniform performance of the composite thermal insulation material;

[0039] (2) The preparation method of the composite thermal insulation material of ceramic fiber and aerogel of the present invention has good thermal insulation properties. Five samples were taken from the composite thermal insulation material of ceramic fiber and aerogel prepared by the present invention, and the average thermal conductivity was 0.027-0.029 W / (m·K);

[0040] (3) The preparation method of the composite thermal insulation material of ceramic fiber and aerogel of the present invention has good hydrophobicity. Five samples were taken from the composite thermal insulation material of ceramic fiber and aerogel prepared by the present invention, and the average water contact angle was 130.2-132.3°;

[0041] (4) The preparation method of the composite thermal insulation material of ceramic fiber and aerogel of the present invention, the prepared composite thermal insulation material has uniform performance, 5 samples were taken from the composite thermal insulation material of ceramic fiber and aerogel prepared by the present invention, the difference between the maximum thermal conductivity and the minimum thermal conductivity was 0.02-0.03 W / (m·K), and the difference between the maximum water contact angle and the minimum water contact angle was 1.2-1.6°;

[0042] (5) The method for preparing the composite thermal insulation material of ceramic fiber and aerogel of the present invention has good toughness and no cracks at the bending position after being bent at 30°;

[0043] (6) The method for preparing the composite thermal insulation material of ceramic fiber and aerogel of the present invention has good durability. After the composite thermal insulation material of ceramic fiber and aerogel prepared by the present invention is left to stand at 800°C for 10 days, there is no problem of particle shedding;

[0044] (7) The preparation method of the composite thermal insulation material of ceramic fiber and aerogel of the present invention has good thermal shock resistance. The composite thermal insulation material of ceramic fiber and aerogel prepared by the present invention is heated to 1200°C for 4 hours, kept at 1200°C for 10 minutes, and then cooled to 20°C by cold air. This is regarded as one cycle. After 20 cycles in total, no cracks exist on the surface.

[0045] (8) The method for preparing the composite thermal insulation material of ceramic fiber and aerogel of the present invention has good high temperature resistance. Five samples were taken from the composite thermal insulation material of ceramic fiber and aerogel prepared by the present invention, and the average thermal conductivity at 1000°C was 0.036-0.038W / (m·K). DETAILED DESCRIPTION

[0046] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0047] Example 1

[0048] A method for preparing a composite thermal insulation material of ceramic fiber and aerogel, specifically comprising:

[0049] 1. Prepare primary aerogel solution:

[0050] (1) Preparation of coated graphite: 200 mL of silica sol and 6 mL of γ-aminopropyltriethoxysilane were mixed, and the mixture was stirred and refluxed at 400 rpm for 5 h at 40°C. 34 g of graphite powder was added, and the mixture was stirred and refluxed for 1 h. The mixture was centrifuged at a centrifugal speed of 6000 rpm for 5 min. The precipitate was washed 3 times with deionized water and dried to obtain coated graphite.

[0051] The particle size of the graphite powder is 50 μm;

[0052] The average particle size of silicon dioxide in the silica sol is 22 nm, the pH is 9, and the mass content of silicon dioxide is 30%;

[0053] (2) Mixing: 2000 mL of silica sol and 60 mL of γ-aminopropyltriethoxysilane were mixed, and the mixture was stirred and refluxed at 40°C and 400 rpm for 5 h. 50 g of coated graphite and 15 g of nickel sulfate were added, and the mixture was stirred and refluxed for 50 min to obtain a primary aerogel solution.

[0054] The average particle size of silicon dioxide in the silica sol is 22 nm, the pH is 9, and the mass content of silicon dioxide is 30%;

[0055] 2. Primary treatment: Add the silicon carbide fiber felt to the mold, add the mold to the vacuum device, evacuate the vacuum device to a vacuum degree of 100Pa, add the primary aerogel solution to ensure that the silicon carbide fiber felt can be completely immersed in the primary aerogel solution and let it stand for 30 minutes; then add it to the oven, control the temperature of the oven to 100°C, and let it stand for 18 hours; then add it to the tubular furnace, in an argon atmosphere, heat it to 1450°C at a heating rate of 4°C / min, let it stand for 2 hours, and obtain the silicon carbide fiber felt after the primary treatment;

[0056] The weight of the silicon carbide fiber felt is 300 g / m 2 , thickness is 2mm;

[0057] 3. Preparation of secondary aerogel solution: 2000 mL of silica sol and 100 mL of γ-aminopropyltriethoxysilane were mixed, and the mixture was stirred and refluxed at 40° C. and 400 rpm for 6 h to obtain a secondary aerogel solution;

[0058] The average particle size of silicon dioxide in the silica sol is 7 nm, the pH is 10, and the mass content of silicon dioxide is 30%;

[0059] 4. Secondary treatment: add the silicon carbide fiber felt after the primary treatment to the mold, add the mold to the vacuum device, evacuate the vacuum device to a vacuum degree of 100Pa, add the secondary aerogel solution, ensure that the silicon carbide fiber felt can be completely immersed in the secondary aerogel solution and let it stand for 50 minutes; then add it to the oven, control the temperature of the oven to 50°C, and let it stand for 50 minutes; then completely immerse it in anhydrous ethanol and let it stand at 50°C for 70 hours, during which the anhydrous ethanol is replaced every 10 hours to obtain the silicon carbide fiber felt after the secondary treatment;

[0060] 5. Preparation of modified silicon carbide whisker suspension: 100 g of β-type silicon carbide whisker, 50 mL of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, and 900 mL of anhydrous ethanol were mixed, and the mixture was stirred and refluxed at 60°C at a stirring speed of 100 rpm for 3 h, filtered, and the precipitate was washed 3 times with anhydrous ethanol, dried, and then mixed with 8700 mL of methanol, and stirred at room temperature at a stirring speed of 100 rpm for 20 min to obtain a modified silicon carbide whisker suspension;

[0061] The length of the β-type silicon carbide whisker is 20 μm and the diameter is 1 μm;

[0062] 6. Composite: In an argon atmosphere, completely immerse the secondary treated silicon carbide fiber felt in a modified silicon carbide whisker suspension, and control the mass volume ratio of the secondary treated silicon carbide fiber felt to the modified silicon carbide whisker suspension to be 300g:3000mL, and let it stand at 55°C for 5h; then add it to a high-pressure reactor, use carbon dioxide for supercritical drying, control the temperature of the high-pressure reactor to 50°C, control the pressure to 12MPa, and let it stand for 2.5h; finally, add it to a tubular furnace, in an argon atmosphere, heat it to 800°C at a heating rate of 4°C / min, and let it stand for 2h to obtain a composite thermal insulation material.

[0063] This embodiment also provides a composite thermal insulation material prepared by the aforementioned preparation method.

[0064] Example 2

[0065] A method for preparing a composite thermal insulation material of ceramic fiber and aerogel, specifically comprising:

[0066] 1. Prepare primary aerogel solution:

[0067] (1) Preparation of coated graphite: 205 mL of silica sol and 6.5 mL of γ-aminopropyltriethoxysilane were mixed, and the mixture was stirred and refluxed at 42°C at a stirring speed of 500 rpm for 5.5 h. 35 g of graphite powder was added, and the mixture was stirred and refluxed for 1.5 h. The mixture was centrifuged at a centrifugal speed of 6500 rpm for 5 min. The precipitate was washed 3 times with deionized water and dried to obtain coated graphite.

[0068] The particle size of the graphite powder is 50 μm;

[0069] The average particle size of silicon dioxide in the silica sol is 22 nm, the pH is 9, and the mass content of silicon dioxide is 30%;

[0070] (2) Mixing: 2050 mL of silica sol and 65 mL of γ-aminopropyltriethoxysilane were mixed, and the mixture was stirred and refluxed at 42 °C at a stirring speed of 500 rpm for 5.5 h. 52 g of coated graphite and 15.5 g of nickel sulfate were added, and the mixture was stirred and refluxed for 55 min to obtain a primary aerogel solution.

[0071] The average particle size of silicon dioxide in the silica sol is 22 nm, the pH is 9, and the mass content of silicon dioxide is 30%;

[0072] 2. Primary treatment: Add the silicon carbide fiber felt to the mold, add the mold to the vacuum device, evacuate the vacuum device to a vacuum degree of 150Pa, add the primary aerogel solution to ensure that the silicon carbide fiber felt can be completely immersed in the primary aerogel solution and let it stand for 35 minutes; then add it to the oven, control the temperature of the oven to 100°C, and let it stand for 19 hours; then add it to the tubular furnace, in an argon atmosphere, heat it to 1500°C at a heating rate of 4°C / min, let it stand for 2 hours, and obtain the silicon carbide fiber felt after the primary treatment;

[0073] The weight of the silicon carbide fiber felt is 300 g / m 2 , thickness is 2mm;

[0074] 3. Preparation of secondary aerogel solution: 2050 mL of silica sol and 110 mL of γ-aminopropyltriethoxysilane were mixed, and the mixture was stirred and refluxed at 42° C. at a stirring speed of 500 rpm for 6.5 h to obtain a secondary aerogel solution;

[0075] The average particle size of silicon dioxide in the silica sol is 7 nm, the pH is 10, and the mass content of silicon dioxide is 30%;

[0076] 4. Secondary treatment: add the silicon carbide fiber felt after the primary treatment to the mold, add the mold to the vacuum device, evacuate the vacuum device to a vacuum degree of 150Pa, add the secondary aerogel solution, ensure that the silicon carbide fiber felt can be completely immersed in the secondary aerogel solution and stand for 55 minutes; then add it to the oven, control the temperature of the oven to 52°C, and stand for 55 minutes; then completely immerse it in anhydrous ethanol and stand at 52°C for 72 hours, during which the anhydrous ethanol is replaced every 11 hours to obtain the silicon carbide fiber felt after the secondary treatment;

[0077] 5. Preparation of modified silicon carbide whisker suspension: 105 g of β-type silicon carbide whisker, 55 mL of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, and 1000 mL of anhydrous ethanol were mixed, and the mixture was stirred and refluxed at 62°C at a stirring speed of 150 rpm for 3.5 h, filtered, and the precipitate was washed 3 times with anhydrous ethanol, dried, and then mixed with 8800 mL of methanol, and stirred at a stirring speed of 150 rpm at room temperature for 25 min to obtain a modified silicon carbide whisker suspension;

[0078] The length of the β-type silicon carbide whisker is 20 μm and the diameter is 1 μm;

[0079] 6. Composite: In an argon atmosphere, completely immerse the secondary treated silicon carbide fiber felt in a modified silicon carbide whisker suspension, and control the mass volume ratio of the secondary treated silicon carbide fiber felt to the modified silicon carbide whisker suspension to be 300g:3100mL, and let it stand at 58°C for 5.5h; then add it to a high-pressure reactor, use carbon dioxide for supercritical drying, control the temperature of the high-pressure reactor to 50°C, control the pressure to 12MPa, and let it stand for 2.5h; finally, add it to a tubular furnace, in an argon atmosphere, heat it to 820°C at a heating rate of 5°C / min, and let it stand for 2.5h to obtain a composite thermal insulation material.

[0080] This embodiment also provides a composite thermal insulation material prepared by the aforementioned preparation method.

[0081] Example 3

[0082] A method for preparing a composite thermal insulation material of ceramic fiber and aerogel, specifically comprising:

[0083] 1. Prepare primary aerogel solution:

[0084] (1) Preparation of coated graphite: 210 mL of silica sol and 7 mL of γ-aminopropyltriethoxysilane were mixed, and the mixture was stirred and refluxed at 45°C at a stirring speed of 600 rpm for 6 h. 36 g of graphite powder was added, and the mixture was stirred and refluxed for 1.5 h. The mixture was centrifuged at a centrifugal speed of 7000 rpm for 6 min. The precipitate was washed 4 times with deionized water and dried to obtain coated graphite.

[0085] The particle size of the graphite powder is 50 μm;

[0086] The average particle size of silicon dioxide in the silica sol is 22 nm, the pH is 9, and the mass content of silicon dioxide is 30%;

[0087] (2) Mixing: 2100 mL of silica sol and 70 mL of γ-aminopropyltriethoxysilane were mixed, and the mixture was stirred and refluxed at 45 °C at a stirring speed of 600 rpm for 6 h. 55 g of coated graphite and 16 g of nickel sulfate were added, and the mixture was stirred and refluxed for 60 min to obtain a primary aerogel solution.

[0088] The average particle size of silicon dioxide in the silica sol is 22 nm, the pH is 9, and the mass content of silicon dioxide is 30%;

[0089] 2. Primary treatment: Add the silicon carbide fiber felt to the mold, add the mold to the vacuum device, evacuate the vacuum device to a vacuum degree of 200Pa, add the primary aerogel solution to ensure that the silicon carbide fiber felt can be completely immersed in the primary aerogel solution and let it stand for 40 minutes; then add it to the oven, control the temperature of the oven to 100°C, and let it stand for 20 hours; then add it to the tubular furnace, in an argon atmosphere, heat it to 1550°C at a heating rate of 5°C / min, let it stand for 2.5 hours, and obtain the silicon carbide fiber felt after the primary treatment;

[0090] The weight of the silicon carbide fiber felt is 300 g / m 2 , thickness is 2mm;

[0091] 3. Preparation of secondary aerogel solution: 2100 mL of silica sol and 120 mL of γ-aminopropyltriethoxysilane were mixed, and the mixture was stirred and refluxed at 45° C. and 600 rpm for 7 h to obtain a secondary aerogel solution;

[0092] The average particle size of silicon dioxide in the silica sol is 7 nm, the pH is 10, and the mass content of silicon dioxide is 30%;

[0093] 4. Secondary treatment: add the silicon carbide fiber felt after the primary treatment to the mold, add the mold to the vacuum device, evacuate the vacuum device to a vacuum degree of 200Pa, add the secondary aerogel solution, ensure that the silicon carbide fiber felt can be completely immersed in the secondary aerogel solution and stand for 60 minutes; then add it to the oven, control the temperature of the oven to 55°C, and stand for 60 minutes; then completely immerse it in anhydrous ethanol and stand at 55°C for 75 hours, during which the anhydrous ethanol is replaced every 12 hours to obtain the silicon carbide fiber felt after the secondary treatment;

[0094] 5. Preparation of modified silicon carbide whisker suspension: 110 g of β-type silicon carbide whisker, 60 mL of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, and 1100 mL of anhydrous ethanol were mixed, and the mixture was stirred and refluxed at 65°C at a stirring speed of 200 rpm for 4 h, filtered, and the precipitate was washed 4 times with anhydrous ethanol, dried, and then mixed with 9000 mL of methanol, and stirred at a stirring speed of 200 rpm for 30 min at room temperature to obtain a modified silicon carbide whisker suspension;

[0095] The length of the β-type silicon carbide whisker is 20 μm and the diameter is 1 μm;

[0096] 6. Composite: In an argon atmosphere, completely immerse the silicon carbide fiber felt after the secondary treatment in the modified silicon carbide whisker suspension, and control the mass volume ratio of the silicon carbide fiber felt after the secondary treatment to the modified silicon carbide whisker suspension to be 300g:3200mL, and let it stand at 60°C for 5.5h; then add it to a high-pressure reactor, use carbon dioxide for supercritical drying, control the temperature of the high-pressure reactor to 50°C, control the pressure to 12MPa, and let it stand for 3h; finally, add it to a tubular furnace, in an argon atmosphere, heat it to 850°C at a heating rate of 5°C / min, let it stand for 2.5h, and obtain a composite thermal insulation material.

[0097] This embodiment also provides a composite thermal insulation material prepared by the aforementioned preparation method.

[0098] Comparative Example 1

[0099] On the basis of Example 1, the step of preparing the primary aerogel solution in step 1 and the step of primary treatment in step 2 were omitted; and in the step of secondary treatment in step 4, an untreated aerogel solution with a gram weight of 300 g / m 2 , the silicon carbide fiber felt with a thickness of 2 mm replaces the silicon carbide fiber felt after the one-time treatment.

[0100] The remaining operations are the same as those in Example 1.

[0101] Comparative Example 2

[0102] On the basis of Example 1, the step 5 of preparing the modified silicon carbide whisker suspension and the step 6 of compounding are omitted; and the silicon carbide fiber felt after secondary treatment obtained in the step 4 of secondary treatment is used as a composite thermal insulation material.

[0103] The remaining operations are the same as those in Example 1.

[0104] Performance Test 1

[0105] Five samples were taken from the composite thermal insulation materials prepared in Examples 1-3 and Comparative Examples 1-2, with an interval of 20 cm between each sample. The thermal conductivity and water contact angle of the five samples were then tested, and the average thermal conductivity and average water contact angle were calculated, respectively. The difference between the maximum thermal conductivity and the minimum thermal conductivity, and the difference between the maximum water contact angle and the minimum water contact angle were calculated, and the calculation results are shown in Table 1:

[0106] Table 1

[0107]

[0108] Performance Test 2

[0109] The composite heat insulating materials prepared in Examples 1-3 and Comparative Examples 1-2 were bent 30° to observe whether there were cracks at the bend. The observation results are shown in Table 2:

[0110] Table 2

[0111]

[0112] Performance Test 3

[0113] After the composite thermal insulation materials prepared in Examples 1-3 and Comparative Examples 1-2 were left to stand at 800° C. for 10 days, it was observed whether the composite thermal insulation materials had a particle shedding problem. The observation results are shown in Table 3:

[0114] Table 3

[0115]

[0116] Performance Test 4

[0117] The composite thermal insulation materials prepared in Examples 1-3 and Comparative Examples 1-2 were heated to 1200°C for 4 hours, kept at 1200°C for 10 minutes, and then cooled to 20°C by cold air. This was considered as one cycle. A total of 20 cycles were performed to observe whether there were cracks on the surface of the composite thermal insulation materials. The observation results are shown in Table 4:

[0118] Table 4

[0119]

[0120] Performance Test 5

[0121] Five samples were taken from the composite thermal insulation materials prepared in Examples 1-3 and Comparative Examples 1-2, with the interval between each sample being 20 cm. The thermal conductivity of the five samples at 1000° C. was then tested, and the average thermal conductivity at 1000° C. was calculated. The calculation results are shown in Table 5:

[0122] Table 5

[0123]

[0124] It can be seen from the results of performance tests 1-5 that the thermal insulation, hydrophobicity, toughness, durability, thermal shock resistance and high temperature resistance of the composite thermal insulation material prepared in Comparative Example 1 are lower than those in Example 1, the hydrophobicity, toughness, durability, thermal shock resistance and high temperature resistance of the composite thermal insulation material prepared in Comparative Example 3 are lower than those in Example 1, and the composite thermal insulation materials prepared in Comparative Examples 1-2 also have the problem of uneven performance.

[0125] Unless otherwise specified, all percentages used in the present invention are by mass.

[0126] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite thermal insulation material of ceramic fiber and aerogel, characterized in that: The method comprises the following steps: preparing a primary aerogel solution, performing a primary treatment, preparing a secondary aerogel solution, performing a secondary treatment, preparing a modified silicon carbide whisker suspension, and compounding; The preparation of the primary aerogel solution comprises the following steps: preparing coated graphite, mixing; The coated graphite is prepared by mixing silica sol and γ-aminopropyltriethoxysilane, stirring and refluxing at 40-45° C., adding graphite powder, continuing to stir and reflux, centrifuging, washing the precipitate, and drying to obtain the coated graphite; The mixing comprises mixing the silica sol and γ-aminopropyltriethoxysilane, stirring and refluxing at 40-45° C., adding coated graphite and nickel sulfate, and continuing to stir and reflux to obtain a primary aerogel solution; The primary treatment comprises adding the silicon carbide fiber felt into a mold, adding the mold into a vacuum device, adding a primary aerogel solution, ensuring that the silicon carbide fiber felt can be completely immersed in the primary aerogel solution and allowing it to stand in a vacuum; then adding the silicon carbide fiber felt into an oven for heat treatment, and then adding the silicon carbide fiber felt into a tubular furnace for high-temperature treatment to obtain a silicon carbide fiber felt after the primary treatment; In the primary treatment, the high temperature treatment is carried out in an argon atmosphere, heating the temperature to 1450-1550°C at a heating rate of 4-5°C / min, and standing for 2-2.5h; The secondary aerogel solution is prepared by mixing silica sol and γ-aminopropyltriethoxysilane, stirring and refluxing at 40-45° C. to obtain a secondary aerogel solution; The secondary treatment comprises adding the silicon carbide fiber felt after the primary treatment into a mold, adding the mold into a vacuum device, adding a secondary aerogel solution, ensuring that the silicon carbide fiber felt can be completely immersed in the secondary aerogel solution and allowing it to stand in a vacuum; then adding it into an oven for heat treatment; and then completely immersing it in anhydrous ethanol for aging treatment to obtain the silicon carbide fiber felt after the secondary treatment; The modified silicon carbide whisker suspension is prepared by mixing β-type silicon carbide whiskers, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and anhydrous ethanol, stirring and refluxing at 60-65° C., filtering, washing the precipitate, drying, and then mixing with methanol and stirring at room temperature to obtain the modified silicon carbide whisker suspension; The composite comprises: in an argon atmosphere, completely immersing the secondary treated silicon carbide fiber felt in a modified silicon carbide whisker suspension, and standing at 55-60° C.; then adding it to a high-pressure reactor and using carbon dioxide for supercritical drying; and finally adding it to a tubular furnace for high-temperature treatment to obtain a composite thermal insulation material; In the composite, the high temperature treatment is carried out in an argon atmosphere, heating the temperature to 800-850° C. at a heating rate of 4-5° C. / min, and standing for 2-2.5 hours.

2. The method for preparing a composite thermal insulation material of ceramic fiber and aerogel according to claim 1, characterized in that: In the preparation of the coated graphite, the volume mass ratio of silica sol, γ-aminopropyltriethoxysilane and graphite powder is 200-210 mL: 6-7 mL: 34-36 g; The particle size of the graphite powder is 50 μm; The average particle size of silicon dioxide in the silica sol is 22 nm, the pH value is 9, and the mass content of silicon dioxide is 30%.

3. The method for preparing a composite thermal insulation material of ceramic fiber and aerogel according to claim 1, characterized in that: In the mixture, the volume mass ratio of silica sol, γ-aminopropyltriethoxysilane, coated graphite and nickel sulfate is 2000-2100 mL: 60-70 mL: 50-55 g: 15-16 g; The average particle size of silicon dioxide in the silica sol is 22 nm, the pH value is 9, and the mass content of silicon dioxide is 30%.

4. The method for preparing a composite thermal insulation material of ceramic fiber and aerogel according to claim 1, characterized in that: In the one-time treatment, the vacuum degree of the vacuum tank during the vacuum standing is 100-200 Pa, and the vacuum standing time is 30-40 minutes; The temperature of the oven during the heat treatment is 100-110°C, and the heat treatment time is 18-20h; The weight of the silicon carbide fiber felt is 300 g / m 2 , thickness is 2mm.

5. The method for preparing a composite thermal insulation material of ceramic fiber and aerogel according to claim 1, characterized in that: In the preparation of the secondary aerogel solution, the volume ratio of silica sol and γ-aminopropyltriethoxysilane is 2000-2100:100-120; The average particle size of silicon dioxide in the silica sol is 7 nm, the pH is 10, and the mass content of silicon dioxide is 30%.

6. The method for preparing a composite thermal insulation material of ceramic fiber and aerogel according to claim 1, characterized in that: In the secondary treatment, the vacuum degree of the vacuum tank during the vacuum standing is 100-200Pa, and the vacuum standing time is 50-60min; The temperature of the oven during the heat treatment is 50-55°C, and the heat treatment time is 50-60min; The temperature during the aging treatment is 50-55° C., the aging treatment time is 70-75 hours, and the anhydrous ethanol is replaced every 10-12 hours.

7. The method for preparing a composite thermal insulation material of ceramic fiber and aerogel according to claim 1, characterized in that: In the preparation of the modified silicon carbide whisker suspension, the mass volume ratio of β-type silicon carbide whisker, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, anhydrous ethanol and methanol is 100-110 g: 50-60 mL: 900-1100 mL: 8700-9000 mL; The length of the β-type silicon carbide whisker is 20 μm and the diameter is 1 μm.

8. The method for preparing a composite thermal insulation material of ceramic fiber and aerogel according to claim 1, characterized in that: In the composite, the mass volume ratio of the silicon carbide fiber felt after secondary treatment to the modified silicon carbide whisker suspension is 300g:3000-3200mL; The temperature of the high-pressure reactor during supercritical drying is 45-50° C., the pressure is 10-12 MPa, and the supercritical drying time is 2.5-3 h.

9. A composite thermal insulation material prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • A high-temperature resistant Si-CO aerogel thermal insulation composite material and its preparation method

    CN102276236A

  • Ultra-light heat-insulating and scouring-resistant functional integrated composite material and preparation method thereof

    CN113246556A